The effects of intratesticular injection of sodium chloride on liveweights, reproductive characteristics, and histological appearance of testes in goat kids - Gökdal, Özdal; Eren, Vadullah; Eren, Ülker; Özuğur, Ali Kemali; Atay, Okan (Acta Scientiarum. Animal Sciences, 2023)
The aim of this study was to investigate the effectiveness of intratesticular injection (ITI) of sodium chloride (NaCl) at two different concentrations for supressing reproductive development in goat kids at two months of age. The experiment was carried out at the experimental unit of Aydın Adnan Menderes University, Çine Vocational School, located in Çine, Aydın, Turkey. The experimental groups were control (C, n = 9), a single ITI of 20% NaCl (T1, n = 8) or 40% NaCl (T2, n = 8). The growth, reproductive characteristics, and histological appearance of the testis in the kids were examined up to nine months of age in different periods. The live weights, scrotal circumference, semen and sexual behavior characteristics were not different among groups. The histogical findings were observed in both testes at nine months of age. Greater intensity of destruction was observed in the testes of T1 and T2 kids than that of C kids. High levels of tubular degeneration were detected in testicular tissue samples in T1 and T2 groups. Based on the results, however, it was concluded that neither 20 nor 40% concentrations of NaCl did ensure the castration effect in the goat kids.